The effect of neem (Azadirachta indica) leaf meal on the growth performance and carcass characteristics of broiler chickens - Ayoola, A. A.; Egbeyale, L. T.; Ekunseitan, D. A.; Adegoke, A. V.; Adeyeri, O. P. (Nigerian Journal of Animal Production, 2015)
A feeding trial was conducted for 56days to investigate the effect of neem (Azadirachta indica) leaf meal on the growth performance and carcass traits of broiler chickens. The neem leaf meal was used in replacing parts of wheat offal in the diets of 192 day-old broiler chickens fed ad libitum at 0.1, 0.2 and 0.3% levels of inclusion. The experimental birds were randomly distributed into four treatments. Each treatment was sub-divided into three replicates of sixteen (16) birds. Medications were administered only to the birds in treatment 1(control group) while vaccination was administered across the treatment during the course of the experiment. Growth parameters were taken on weekly basis and data obtained were subjected to one way analysis of variance (ANOVA) in a completely randomized design. There was a significant (P<0.05) effect of varying dietary inclusion of NLM only on average weight gain among the birds at the starter phase. Groups fed 0.3% NLM recorded the highest average weight gain (430.63g) as against 421.00, 392.57 and 394.97g recorded for the control, 0.1% and 0.2% NLM groups, respectively. Neem leaf meal had nosignificant (P<0.05) effect on broiler performance at the finisher phase across the treatment groups. Mortality was not affected (P>0.05) at any of the growth phases. Carcass traits; cut-parts (except neck) and organs showed no influence (P>0.05) of NLM inclusion. It can then be recommended that the neem leaf meal inclusion up to 0.3% in the diets of the broiler chickens can be used as growth promoters during the chick phase of growth.